2018
DOI: 10.1177/1557988318821512
|View full text |Cite
|
Sign up to set email alerts
|

Men’s Help-Seeking Attitudes in Rural Communities Affected by a Natural Disaster

Abstract: The article describes a mixed methods study of help-seeking in men living in the Chilean Central Valley, following exposure to a major earthquake event in 2010. The results identify that, within the sample, positive attitudes toward help-seeking correlated with younger age, higher education levels, above-average incomes, and stable personal relationships. It appears that education plays a significant role in shaping such positive attitudes, particularly by influencing views of gender roles and help-seeking. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Help-seeking within this study was dependent on capacity of the individual at that time and their insight into their current acute need, and a few barriers were identified. Barriers include a lack of information regarding available services, doubts about privacy and confidentiality, negative experiences of health services, stigma, and isolation ( Kaukiainen & Kõlves, 2020 ; Labra et al, 2019 ; Trail et al, 2021 ). There were also enablers of help-seeking, which were reinforced by Labra et al (2019) , who indicated that a spouse or women, in particular, play a crucial role in assisting men to decide when to seek help.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Help-seeking within this study was dependent on capacity of the individual at that time and their insight into their current acute need, and a few barriers were identified. Barriers include a lack of information regarding available services, doubts about privacy and confidentiality, negative experiences of health services, stigma, and isolation ( Kaukiainen & Kõlves, 2020 ; Labra et al, 2019 ; Trail et al, 2021 ). There were also enablers of help-seeking, which were reinforced by Labra et al (2019) , who indicated that a spouse or women, in particular, play a crucial role in assisting men to decide when to seek help.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the sample included a male participant’s significant other, such as a partner, spouse, close relative, or friend. It was vital to invite significant others to participate given they often play an important role for men to seek help ( Labra et al, 2019 ). However, it was not compulsory for the significant other to participate.…”
Section: Methodsmentioning
confidence: 99%
“…Medical professionals could be biased in their approach to analyzing symptoms and diagnosing diseases in older male patients [ 32 ]. In Japanese culture, masculinity may be dominant among the older generation; therefore, older male patients do not visit hospitals with mild symptoms [ 33 , 34 ]. The severity of the symptoms might explain why we observed a trend of early diagnosis in older male patients.…”
Section: Discussionmentioning
confidence: 99%
“…Social factors such as age, gender, living location, and relationships with others in the community affect the tendency to use lay or professional care [ 6 , 7 , 8 ]. HSBs can affect people’s health conditions, such as self-rated health and quality of life (QOL) [ 6 , 9 , 10 ]. Hence, it is important to consider HSBs to improve healthcare.…”
Section: Introductionmentioning
confidence: 99%